Development of an On-Column Trace Enrichment Method for the Determination of Sub-μg/L Bisphenol A in Bottled Water by RP-HPLC with Fluorescent Detection - Kevin C. Honeychurch (International Journal of Analytical Chemistry)
A simple extraction-free, on-column trace enrichment liquid chromatographic method for the determination of trace levels of bisphenol A (BPA) in bottled water samples has been developed. It was found possible to determine ng/L (ppt) levels of BPA by the direct introduction of 6 mL of sample water to the HPLC column utilising fluorescence detection (Exλ = 274 nm, Emλ = 314 nm). Following the loading of the sample and the chromatographic focusing of the BPA on the analytical column, a simple switch from the aqueous sample to the isocratic chromatographic elution step of 50% acetonitrile/deionised water was undertaken. Using a BPA concentration of 0.596 μg/L the effect of sample volume was investigated over the range 1.0 to 12 mL. A linear relationship with the sample volume introduced to the HPLC column and the resulting peak height for BPA was found over the entire range investigated R2=0.999. Using a sample volume of 6.0 mL, a well-defined chromatographic peak was recorded for BPA over the concentration range of 0.1 μg/L to 6.25 μg/L R2=0.9998. A limit of detection of 0.058 μg/L for BPA was calculated based on 3 δ. A mean recovery of 100% with an associated %CV of 7.6% (n = 5) was obtained for a bottled spring water sample fortified with 1.25 μg/L BPA. Samples can be processed in under 12 minutes, much faster than that commonly reported for conventional offline extraction and chromatographic-based methods. The results show that the optimised method holds promise for the determination of BPA in such samples.